Уравнение:x³+ax²+ba+c=0
x²+px+q=0⇒x1+x2=-p U x1*x2=q
{x1²+x1x2+x2²=-a
{x1²x1x2+x1²x2²+x1x2x2²=b
{x1²x1x2x2²=-3
отсюда следует
{(x1+x2)²-x1x2=-a
{x1³x2+x1²x2²+x1x2³=b
{x1³x2³=-c
отсюда
{(x1+x2)²-x1x2=-a
{x1x2(x1²+x2²)+x1²x2²=b
{x1³x2³=-c
отсюда
{(x1+x2)²-x1x2=-a
{x1x2[(x1+x2)²-2x1x2]+x1²x2²=b
{x1³x2³=-c
отсюда
{(x1+x2)²-x1x2=-a
{x1x2(x1+x2)²-x1²x2²=b
{x1³x2³=-c
подставим х1+х2=-p ,x1*x2=q и получим
{(-p)²-q=-a
{q(-p)²-q²=b
{q³=-c
или
{{a=q-p²
{b=p²q-q²
{c=-q³
подставим в кубическое уравнение
x³+(q-p²)x²+)p²q-q²)x-q³=0